ANALISIS RISIKO HUKUM PENGGUNAAN ROBO-ADVISOR DALAM INVESTASI SAHAM SYARIAH: STUDI ASPEK GHARAR DAN MAYSIR - Yuniartik Yuniartik (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
The development of financial technology (FinTech) has introduced innovations such as Robo-Advisors, digital platforms providing algorithm-based investment management services. In the Sharia capital market, the use of Robo-Advisors presents new challenges concerning compliance with Sharia principles, specifically the prohibition of Gharar (uncertainty) and Maysir (gambling). This research aims to analyze the legal risks of using Robo-Advisors in Sharia stock investment in Indonesia through a normative-juridical approach. The findings indicate that Gharar risk arises from the "black box" nature of the algorithms, where investors do not fully understand the basis of investment decision-making transparently. Meanwhile, Maysir risk can be detected if the algorithm encourages speculative high-frequency trading (churning). From a regulatory perspective, the Financial Services Authority (OJK) and the National Sharia Board-Indonesian Ulema Council (DSN-MUI) need to strengthen algorithm audit standards to ensure that Robo-Advisor operations remain within the valid framework of the wakalah bil ujrah contract without manipulative elements.